Is household smoking a risk factor for caries? A case-control study - Zurina, A.M.; Asma, Mohamed; Raja-Latifah, Raja Jallaludin; Yusoff, Noriah (Penerbit Universiti Kebangsaan Malaysia, 2014)
Recent studies suggested that exposure to household smoking (HHS) could be a modifiable risk factor for caries development among children. Majority of the studies were cross sectional in nature. Therefore, a case-control study was designed to test the hypothesis that HHS is a risk factor to caries experience in permanent teeth. Calculation of sample size was based on the ratio of 1 case to 4 controls. Case was defined as a child aged 13-14 years old with caries in at least one second permanent molar and control was defined as a child from the same age and school with no caries second permanent molars. Matching was done for gender and ethnicity. School dental records provided information on oral health status and oral hygiene status. Information on HHS, socio-economic status, child's smoking status and child's oral health practices were obtained from a self administered questionnaire, completed by the children and their parents. The result showed that 55.9% of the case group was exposed to HHS, as compared to 44.1% among the control group. In the final multiple logistic regression model after controlling for important risk factors for caries, children with caries were almost twice as likely to have been exposed to HHS for more than 10 years as compared to children with no caries, (Adjusted OR=1.90 and 95% CI=1.35, 2.60). In addition, children who only received dental care from the school dental service had reduced risk of having dental caries by more than one third (36%) as compared with those who received dental care from school dental service (SDS) as well as had additional dental problem solving visit outside SDS (Adjusted OR=0.64 and 95% CI=0.50, 0.90). It is concluded that exposure to HHS for a long duration (> than 10 years) increase the risk to have caries experience in permanent teeth of children. Copyright Reserved © Sains Malaysiana.